(untitled) (Revista Interdisciplinar de Marketing, 2025)
While social influencers as streamers promote and endorse brands in social media, we do not know how following the influencer can shape the consumer’s shopping behavior. Twitch.tv is a social media and a live streaming platform for players and gamers. Social influencers work in Twitch.tv aiming influence consumer shopping behavior. Drawing on Social Identity Theory and Endorsement Theory, the authors propose a theoretical framework that consumers following an influencer on social media and buying products used by him/her both moderate the impact of brand recall, trust, and involvement on the total spent in game monthly. We collected data through social media by posting our questionnaire at the Twitch.tv with 270 gamers. The results showed that following the influencer in social media strengthens the main effect of trust and brand recall on total spent in game monthly. Moreover, the greater the number of products bought after seeing an influencer using them, the greater the main effect of trust and involvement on total spent in game monthly. The theoretical reason is because the consumers that buy trustworthy products used by the influencer do so to modify their self-concept and develop relationships with social media celebrities.